2017
DOI: 10.3390/su9081395
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Population Assistance and Returning Home in the Reconstruction Process of the 2009 L’Aquila Earthquake

Abstract: Abstract:The 2009 L'Aquila earthquake left approximately 67,000 homeless people. The earthquake severely damaged facilities, structures, and infrastructure of L'Aquila town, the capital of Abruzzo region, as well as 56 other municipalities in the so-called "crater". The resident population in the crater area at the time of the earthquake included 68,503 inhabitants in the city of L'Aquila and 71,081 in other municipalities of the crater, yielding a total of 139,584 inhabitants. Several solutions were adopted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 16 publications
1
14
0
1
Order By: Relevance
“…Table 17 reports the estimated losses in L'Aquila town and in the whole region affected by the seismic event, considering both the economic impact and the consequences to buildings and people. The results are in a good agreement with the actual ones (Dolce and Manfredi 2015;Dolce and Di Bucci 2017;Mannella et al 2017).…”
Section: Validation Of Real Damage and Loss Scenariossupporting
confidence: 88%
“…Table 17 reports the estimated losses in L'Aquila town and in the whole region affected by the seismic event, considering both the economic impact and the consequences to buildings and people. The results are in a good agreement with the actual ones (Dolce and Manfredi 2015;Dolce and Di Bucci 2017;Mannella et al 2017).…”
Section: Validation Of Real Damage and Loss Scenariossupporting
confidence: 88%
“…Such time is estimated as 161 months (or 13 years and 5 months) after the earthquake. Other studies of the housing recovery process after the 2009 L'Aquila earthquake in Italy (Mannella et al 2017) and the 1992 Hurricane Andrew (Zhang and Peacock 2009) or 2014 South Napa Earthquake (Kang et al 2018) in the United States showed trends that can be comparable with an exponential curve. Nonetheless, more case studies affected by the 2012 NIE should be investigated in order to validate the approach used in this work.…”
Section: Housing Recovery: Comparison Of Two Case Studiesmentioning
confidence: 93%
“…The loss of these residential resources will displace those living within them and place pressure on surrounding housing resources, with this pressure being exacerbated if an influx of rebuild workers follows during the post-earthquake recovery phase (Taylor et al, 2012). In L’Aquila around 63,000 people became homeless due to the earthquake, of which approximately 7000 people had their 1627 residential buildings within the L’Aquila cordon (Alexander, 2013; Mannella et al, 2017). As of 2017, 35% of the displaced central L’Aquila residents were still waiting to return to their homes (Mannella et al, 2017).…”
Section: Downstream Consequences: Social Impactsmentioning
confidence: 99%
“…In L’Aquila around 63,000 people became homeless due to the earthquake, of which approximately 7000 people had their 1627 residential buildings within the L’Aquila cordon (Alexander, 2013; Mannella et al, 2017). As of 2017, 35% of the displaced central L’Aquila residents were still waiting to return to their homes (Mannella et al, 2017). Although many of these residents would have been displaced regardless of the cordon (92% of buildings in central L’Aquila suffered damage), it remains useful to identify some of the issues that arose with post-earthquake homelessness, as a cordon involving residential buildings will contribute to this effect (Mannella et al, 2017).…”
Section: Downstream Consequences: Social Impactsmentioning
confidence: 99%